Effect of ellipticity of optical eigenwaves on the enhancement of efficiency of acousto-optic Bragg diffraction. A case of optically active Pb5Ge3O11 crystals - Oksana Mys; Myroslav Kostyrko; Dmytro Adamenko; Iryna Martynyuk-Lototska; Ihor Skab; Rostyslav Vlokh (AIP Advances, 2022)
We show that the existence of optical activity in an optical material can lead to essential enhancement of acousto-optic (AO) figure of merit. The reason is that the ellipticity of interacting optical eigenwaves approaches unity near the optical axis and so additional elasto-optic (EO) tensor components become involved in the effective EO coefficient. We demonstrate on lead germanate crystals that the increase in the efficiency of AO diffraction manifests itself for all types of AO interactions whenever the incident optical wave propagates close to the optical axis. In the particular case of diffraction in the interaction plane XZ of Pb5Ge3O11 crystals, the maximal enhancement of the AO figure of merit takes place under conditions of the isotropic diffraction of ordinary and extraordinary optical waves with a pure transverse acoustic wave (AW) polarized parallel to the Y axis (a so-called AW PT2), with the AO figure of merit increasing from zero to 7.5 × 10−17 s3/kg, and the types of anisotropic diffraction on the AWs QT1 and PT2 when the AO figure of merit increases twice (e.g., from 7.6 × 10−17 to 1.5 × 10−16 s3/kg). The maximal AO efficiency in the interaction plane XZ is reached at types I and II of the isotropic AO interactions of ordinary and extraordinary optical waves with a quasi-longitudinal AW; in these cases, the AO figure of merit increases from 6.8 × 10−15 to 12.4 × 10−15 s3/kg and from 5.6 × 10−15 to 12.4 × 10−15 s3/kg, respectively.